Experiences of clinicians and managers in the implementation of a family focused model in child and adult psychiatry - Linderborg, Camilla; Grant, Anne; Weimand, Bente Margrethe; Falkov, Adrian Farrel; Östman, Margareta (Frontiers in Psychiatry, 2024)
Introduction: This paper describes the process of implementing a family focused model, The Family Model, in child and adolescent and adult mental health services in Sweden.Additionally, it describes a service development project carried out in both services within a defined geographical area of Region Stockholm. The Family Model is a communication tool designed to assist clinicians in both services to have family focused conversations with their patients and relatives. Internationally, the needs of individuals experiencing mental health challenges (parents, children and young people) and their close relatives are now well recognised, but barriers to family focused practice nevertheless persist.The aim of this study was to better understand clinicians` experiences in implementing The Family Model in both services.Methods: Three preplanned focus group interviews were carried out with 14 clinicians and managers across both services and the data were analysed in accordance with methods of Naturalistic inquiry.Result: Findings suggest that The Family Model has utility in both services. The Naturalistic inquiry analyses revealed three main themes: individual, relational and organisational aspects with a total of 10 sub-themes of how the models influence the participants. Furthermore, analyses on a meta understanding level explored that participants underwent a developmental journey in learning about and using The Family Model in practice which was expressed through three themes: "Useful for burdened families", "Influencing prevention", and "To integrate this would be fantastic".The Family Model, when adapted for the Swedish context, is a useful tool for assisting experienced clinicians to engage in family focused practice in both child and adolescent and adult mental health services. The Family Model highlights different aspects in everyday clinical services that were of special interest for clinicians, families, and the system. Future research could explore families' perspectives of the utility of the model.